Multilingual dictionary of fish and fish products = (Fishing News Books, 1995)
Sucessive editions of this remarkable work have facilitated international trade in fish and fish products by making available a comprehensive source of specialised information and general knowledge on fish, other marine life, and fish products in commercial use today.